Mapping TOEFL® Essentials™ Test Scores to the Canadian Language Benchmarks. Issue 1 (22nd October 2022) - Papageorgiou, Spiros; Davis, Larry; Ohta, Renka; Garcia Gomez, Pablo
Abstract : In this research report, we describe a study to map the scores of the TOEFL ® Essentials ™ test to the Canadian Language Benchmarks (CLB). The TOEFL Essentials test is a four‐skills assessment of foundational English language skills and communication abilities in academic and general (daily life) contexts. At the time of writing this report, the test was the most recent addition to the TOEFL® Family of Assessments. TOEFL Essentials test scores are intended to provide academic programs and other users with reliable information regarding the test taker's ability to understand and use English. Mapping of scores to widely used language frameworks such as the CLB provides additional support for interpreting test results and for making inferences regarding test‐taker abilities. The score mapping process consisted of the following steps, as recommended in the literature: (a) establishing construct congruence between the test content and the performance descriptors of the CLB; (b) establishing recommended minimum test scores (cut scores) required to classify language learners into CLB levels, based on the judgments of local experts; and (c) providing evidence of procedural, internal, and external validation of the recommended cut scores. Abstract : Report Number: RR‐22‐16